2017
DOI: 10.1530/eje-17-0485
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular manifestations of primary hyperparathyroidism: a narrative review

Abstract: Data on cardiovascular disease in primary hyperparathyroidism (PHPT) are controversial; indeed, at present, cardiovascular involvement is not included among the criteria needed for parathyroidectomy. Aim of this narrative review is to analyze the available literature in an effort to better characterize cardiovascular involvement in PHPT. Due to physiological effects of both parathyroid hormone (PTH) and calcium on cardiomyocyte, cardiac conduction system, smooth vascular, endothelial and pancreatic beta cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 109 publications
2
77
0
9
Order By: Relevance
“…First, it is known that arterial hypertension is highly prevalent in primary hyperparathyroidism, ranging from 40% to 65%, which is much higher than the expected 25%-30% of hypertension in the general adult population. 70 Given our observations, a possible mechanism could be that increased Ca 2+ in the tubular fluid, as occurs in hypercalcemia, stimulates the activity of NCC promoting NaCl reabsorption and, hence, the development of hypertension. Second, it has been recently demonstrated that glucose and other sugars act as type II calcimimetics, enhancing CaSR affinity for Ca 2+ .…”
Section: Discussionmentioning
confidence: 67%
“…First, it is known that arterial hypertension is highly prevalent in primary hyperparathyroidism, ranging from 40% to 65%, which is much higher than the expected 25%-30% of hypertension in the general adult population. 70 Given our observations, a possible mechanism could be that increased Ca 2+ in the tubular fluid, as occurs in hypercalcemia, stimulates the activity of NCC promoting NaCl reabsorption and, hence, the development of hypertension. Second, it has been recently demonstrated that glucose and other sugars act as type II calcimimetics, enhancing CaSR affinity for Ca 2+ .…”
Section: Discussionmentioning
confidence: 67%
“…Considering the association of urine KIM‐1/uCr with PTH, a direct action of the hormone may be implicated in the process of kidney injury. Chronic PTH excess is indeed known to be associated with endothelial dysfunction and other atherogenic processes through a direct interaction with its receptor on vessels . This action of PTH on the kidney vasculature and a possible direct effect on the proximal tubule cells could presumably be of importance in the pathogenesis of kidney disease in PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…Связь между повышением уровня ПТГ, кальция и риском сердечно-сосудистых заболеваний активно обсуждается в настоящее время, однако механизмы остаются не до конца изученными. Имеются предположения о негативном влиянии повышенного уровня ПТГ через активацию ренин-ангиотензиновой системы, также обсуждается прямое влияние ПТГ на кардиомиоциты и эндотелий сосудов [14][15][16]. Кроме этого, низкая концентрация обеспечения витамином D больных ПГПТ, также может играть отрицательную роль и приводить к более частому развитию ССЗ [17].…”
Section: обсуждение основного результата исследованияunclassified